A Comprehensive Examination of Samuel Beckett's Literary Legacy (International Journal of Food and Nutritional Sciences, 2019)
The study presents a comprehensive analysis of Samuel Beckett's literary contributions, focusing on the intricate interplay between thematic exploration and stylistic choices within his works. The examination centers on seminal pieces like "Waiting for Godot" and "Endgame," unraveling the profound engagement with existential themes that permeate Beckett's narratives. Themes of absurdity, existentialism, isolation, nihilism, and challenges in communication are meticulously explored. Concurrently, the study delves into Beckett's distinctive stylistic features, including stark minimalism, repetition, the use of silence, and linguistic experimentation. Through these deliberate choices, Beckett not only conveys existential depth but also challenges traditional norms of expression. The findings underscore the inseparable connection between thematic richness and stylistic innovation in Beckett's literary legacy. His enduring contribution lies not only in intellectual exploration but in the immersive experiences crafted through the fusion of thematic complexity with innovative literary techniques. This study sheds light on the lasting impact of Beckett's works, reflecting the intricacies of the human condition and reshaping the landscape of literary expression..